Clinical and epidemiological profile of patients with endometriosis in a gynecological service in Espírito Santo: a preliminary study (Brazilian Journal of Health Research, 2025)
Introduction: Endometriosis is a chronic and inflammatory clinical pathology, characterized by the presence of functional endometrial tissue outside the uterus. Objectives: The following article seeks to identify the clinical and epidemiological profile of patients with endometriosis in a reference gynecology service in Espírito Santo, with the aim of sensitizing professionals regarding the suspicion of the presence of the disease. Methods: This is a cross-sectional study involving 130 patients with pelvic pain, aged between 18 and 55 years old, who were submitted to a form to collect epidemiological and clinical data, and then underwent a physical examination and Nuclear Magnetic Resonance Imaging (MRI) for the diagnosis of endometriosis. Results: Of the 130 patients interviewed, 63 had a positive diagnosis of endometriosis. The most frequent symptoms were dysmenorrhea (92%) and dyspareunia (77.7%). The most specific symptoms were dysuria (65.6%) and dyschesia (64.1%). In the epidemiological analysis, 42.9% were aged between 40 – 49 years old, 68.2% were married and 49.2% had completed secondary education. Conclusion: It was possible to identify that the majority of patients were aged between 40 and 49 years old (42.9%), showing a late diagnosis compared to other populations. Among the most common symptoms studied, dysmenorrhea (92%) and dyspareunia (77.7%) were the most sensitive symptoms. Dysuria (65.6%) and pain when evacuating (64.1%) were the most specific. Thus, these associated symptoms can be extremely valuable for clinical suspicion and diagnostic management of cases.
Keywords: Endometriosis; Pelvic Pain; Clinical Epidemiology; Infertility